Pre-asymptotic dynamics of the infinite size Neumann (p = 2 spherical) model - Barbier, Damien (2019)
In this contribution we further study the classical disordered p = 2 spherical model with Hamiltonian dynamics, or in integrable systems terms, the Neumann model, in the infinite size limit. We summarise the asymptotic results that some of us presented in a recent publication, and we deepen the analysis of the pre-asymptotic dynamics. We also discuss the possible description of the asymptotic steady state with a generalised Gibbs ensemble.